Refining the methodology for investigating the relationship between fluency and the use of formulaic language in learner speech - Guz, Ewa (Research in Language, 2016)
This study is a cross-sectional analysis of the relationship between productive fluency and the use of formulaic sequences in the speech of highly proficient L2 learners. Two samples of learner speech were randomly drawn and analysed. Formulaic sequences were identified on the basis of two distinct procedures: a frequency-based, distributional approach which returned a set of recurrent sequences (n-grams) and an intuition and criterion-based, linguistic procedure which returned a set of phrasemes. Formulaic material was then removed from the data. Breakdown and speed fluency measures were obtained for the following types of speech: baseline (pre-removal), formulaic, non-formulaic (postremoval). The results show significant differences between baseline and post-removal fluency scores for both learners. Also, formulaic speech is produced more fluently than non-formulaic speech. However, the comparison of the fluency scores of n-grams and phrasemes returned inconsistent results with significant differences reported only for one of the samples.